Study of the temperature-humidity equivalence and the time-temperature superposition principle in the finite-strain response of polyamide-6 and short glass fibre-reinforced polyamide-6 - Daniele Finazzi; Guillem Seychal; Jean-Marie Raquez; Gilles Robert; Karen De Clerck; Lode Daelemans; Wim Van Paepegem (Polymer Testing)
Polyamide-6 (PA6) and short glass fibre-reinforced PA6 (GPA6) are increasingly used in structural automotive parts exposed to harsh conditions, respectively as liner in Type IV hydrogen tanks and under-the-hood components near the engine. Safe design requires understanding of their complex mechanical behaviour under the influence of temperature, moisture, and strain rate. Two models often applied in the literature are the temperature-humidity equivalence and the time-temperature superposition (TTS), however their accuracy to describe the full mechanical response is still unclear. By generating high-quality data, this paper conducts a quantitative study of these models on the mechanical response of injection-moulded PA6 and GPA6 with a very high fibre content (50 wt%). The materials were conditioned either dry or at 50%RH. Dynamic mechanical analysis (DMA) was used to measure the glass transition temperature of dry PA6 and 50%RH PA6, and to construct TTS master curves. Tensile tests were then conducted at different combinations of temperature, moisture, and strain rate. Comparison of the tensile true stress-true strain curves revealed that the proposed models fail to capture the effects of the thermal history, which may cause microstructural modifications as demonstrated with differential scanning calorimetry (DSC). The link between DSC, DMA, and tensile data constitutes a novelty of this work and was possible because all the samples had the same hygro-thermal history. Additionally, self-heating of PA6 causes deviations from the TTS at large strains. The results of this study may help develop more accurate material models, ultimately improving the design of structural automotive parts.